Decomposing regional business change at plant level in Italy: A novel spatial shift‐share approach. (22nd May 2013) - Espa, Giuseppe; Filipponi, Danila; Giuliani, Diego; Piacentino, Davide
Abstract: In this paper, spatial shift‐share decomposition is analysed when applied to Italian data on regional business change at plant level, over the period 2004–2009. A new type of spatial decomposition, which looks more effectively at neighbourhood influence, is introduced here. Notable results emerge from the empirical investigation. First, it can be seen that the spatial level of aggregation greatly affects results. Second, evidence of neighbourhood advantage in the Southern NUTS 3 regions is found, together with opposite results for the Central‐Northern NUTS 3 regions. Finally, evidence of positive industrial mix effects is only found in Central‐Northern Italy.